The Potential of AI in Improving the Media Role of Audiovisual Content in Oman - Elsawy, Elsayed Salah; Al- Riyami, Ali Said; Attia, Sarah Nagah; Ismaeil, Ayman; Al Meshefri, Helal Salem (Journal of Ecohumanism, 2024)
The study aimed to explore the importance of audiovisual content in enhancing the media functions of media institutions, the obstacles associated with the management and preservation of audiovisual media, and the possibility of benefiting from artificial intelligence to improve the use of audiovisual content. The study focused on the Ministry of Information in the Sultanate of Oman, and relied on the descriptive approach using a survey to identify the importance and benefits of audiovisual content and the challenges of its preservation and management. The survey was distributed using Google Forms to users of audiovisual content in the Ministry of Information. One of the most prominent results of the study is that more than two-thirds of respondents believe that audiovisual content plays an important role in supporting the Ministry of Information in its activities, in addition to its social and cultural value. Among the challenges of managing and preserving audiovisual media content is the lack of a strategy to protect it, and there is a lack of expertise related to preserving audiovisual media. The study suggests using artificial intelligence as a tool to support the archiving of audiovisual media content, and to increase efforts to digitize media materials that have not yet been digitized.